Innovative technologies to address neglected tropical diseases in African settings with persistent sociopolitical instability - Tsegahun Manyazewal; Gail Davey; Charlotte Hanlon; Melanie J. Newport; Michael Hopkins; Jenni Wilburn; Sahar Bakhiet; Leon Mutesa; Agumasie Semahegn; Esubalew Assefa; Abebaw Fekadu (Nature Communications)
Abstract The health, economic, and social burden of neglected tropical diseases (NTDs) in Africa remains substantial, with elimination efforts hindered by persistent sociopolitical instability, including ongoing conflicts among political and ethnic groups that lead to internal displacement and migration. Here, we explore how innovative technologies can support Africa in addressing NTDs amidst such instability, through analysis of WHO and UNHCR data and a systematic literature review. Countries in Africa facing sociopolitical instability also bear a high burden of NTDs, with the continent ranking second globally in NTD burden (33%, 578 million people) and first in internal displacement (50%, 31.6 million people) in 2023. Studies have investigated technologies for their potential in NTD prevention, surveillance, diagnosis, treatment and management. Integrating the evidence, we discuss nine promising technologies—artificial intelligence, drones, mobile clinics, nanotechnology, telemedicine, augmented reality, advanced point-of-care diagnostics, mobile health Apps, and wearable sensors—that could enhance Africa’s response to NTDs in the face of persistent sociopolitical instability. As stability returns, these technologies will evolve to support more comprehensive and sustainable health development. The global health community should facilitate deployment of health technologies to those in greatest need to help achieve the NTD 2030 Roadmap and other global health targets.